The Influence of Audit Findings and Follow-Up on Audit Result Recommendations on Audit Opinions on Regional Government Financial Reports with Regional Government Size as a Moderating Variable - Novialdi, Novialdi; Mukhzarudfa, Mukhzarudfa; Wijaya, Rico (Dinasti Publisher, 2026)
This research purpose to examine the impact of audit findings and follow-up on audit opinions on local government financial statements, as well as to analyze the role of local government size as a moderating variable. The research subjects include local governments headed by Acting Regional Heads in 2023 in Indonesia. The method used is quantitative with a comparative causal approach, with a sample of 255 local governments selected using purposive sampling. Data were obtained from the audit reports of the Supreme Audit Agency and local government financial statements. Logistic regression analysis shows that follow-up on audit recommendations has a partial positive effect on audit opinions, while audit findings and follow-up on recommendations together influence audit opinions. Furthermore, the size of the local government strengthens the relationship between audit findings and follow-up on recommendations on audit opinions, indicating that the capacity and operational scale of local governments have an impact on the effectiveness of improvements and auditors' assessments of public financial management.